Crime in Ireland north and south: Feuding gangs and profiteering paramilitaries - Hourigan, Niamh (Trends in organized crime)
This paper provides a systematic overview of the emergence of organized crime in the Republic of Ireland and Northern Ireland since the late 1960s. It draws on two major studies of organized crime in the South (Hourigan 2011) and paramilitary activity in the North (Morrison 2014) to explore how conflict within and between organized criminal and paramilitary groups, shapes the distinctive dynamic of organized crime on the island of Ireland. The paper opens with an overview of the development of the drugs trade in the Republic of Ireland. The distinctive cultural characteristics of Irish organized crime groups are considered and the role played by paramilitary groups in criminal networks, North and South, is reviewed. As part of this analysis, the dynamic of inter-gang feuds and the spectrum of conflicts between organized criminal and paramilitary groups are analyzed. The competitive and mutually beneficial links between these organizations, North and South are explored as well as the tendency of paramilitaries to engage in vigilantism against criminals (mostly drugs dealers) as a means of building political capital within local communities.